The role of environmental management control systems for ecological sustainability and sustainable performance. Issue 9 (22nd December 2020) - Rehman, Shafique Ur; Bhatti, Anam; Kraus, Sascha; Ferreira, João J. M.
Abstract : Purpose: The purpose of this study determines how environmental management control system (MCS) packages influence ecological sustainability and sustainable performance through the mediating role of environmental strategies. Furthermore, this applies organizational capabilities as moderating variables between environmental strategies, ecological sustainability and sustainable performance in a sample of 373 construction firms. Design/methodology/approach: The authors apply quantitative questionnaire data from construction firm representatives (from project, sales and construction managers and contract managers, executive directors and engineers) to structural equation modeling and SmartPLS for our analysis. Findings: The results demonstrate that recourse to environmental MCS packages significantly influence ecological sustainability, sustainable performance and environmental strategies. Additionally, environmental strategies and organizational capabilities significantly influence ecological sustainability and sustainable performance. Moreover, environmental strategies mediate between environmental MCS packages, ecological sustainability and sustainable performance. Organizational capabilities significantly moderate the relationship between ecological sustainability and sustainable performance. Practical implications: This research highlights the issue of how the management of construction organizations deploy environmental MCS packages, organizational capabilities and business strategies to measure ecological sustainability and improve their sustainable performance. This study fills a gap in the literature and facilitates the management of construction organizations in strengthening their internal resources in terms of environmental MCS packages, environmental strategies and organizational capabilities able to help improve their ecological sustainability and sustainable performance. Originality/value: There are few studies building theoretical frameworks for incorporating environmental MCS packages, organizational capabilities, environmental strategies, ecological sustainability and sustainable performance into a single study. Although the influence of various types of intangible resources on ecological sustainability and sustainable performance receive considerable examination in the literature, there is a dearth of attention paid to understanding the role of environmental MCS packages, environmental strategies and organizational capabilities in determining the ecological sustainability and sustainable performance of construction organizations.